ENTREPRENEURIAL ECOSYSTEM, ENTREPRENEURIAL SELF-EFFICACY, AND ENTREPRENEURIAL INTENTION IN HIGHER EDUCATION: EVIDENCE FROM EAST JAVA - Syahrin, Nabila; Sumaji, Yoseva; Utami, Christina (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
The main objective of this study is to conduct an empirical analysis of the influence of entrepreneurial ecosystem factors (EE) and entrepreneurial self-efficacy (ESE) on entrepreneurial intention (EI). This study also used the role of location as a control variable in this relationship. The population used in this study is among students both in East Java and outside East Java. The sample data obtained by 200 respondents and analyzed using the PLS-SEM approach with the help of Smart PLS 3.0. The results showed that EE had a significant positive effect on student EI. Meanwhile, ESE has a negative influence on EI when directly related, but if treated as a moderator variable, it can strengthen the relationship between EE and EI, although it has not had significant results, To further examine the role of this moderator, the researchers also elaborated the ESE factor with other variables such as Location, Gender, and Age using the ANOVA Two-Way Interaction Test and concluded that ESE can function as Substantial catalysts in encouraging people to embark on entrepreneurial ventures, but the role of the ESE tends to fluctuate, especially as we age.